2021
DOI: 10.1126/sciadv.abe1527
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic regulation of local and long-range input balance drives top-down attentional circuit maturation

Abstract: Cognitive function depends on frontal cortex development; however, the mechanisms driving this process are poorly understood. Here, we identify that dynamic regulation of the nicotinic cholinergic system is a key driver of attentional circuit maturation associated with top-down frontal neurons projecting to visual cortex. The top-down neurons receive robust cholinergic inputs, but their nicotinic tone decreases following adolescence by increasing expression of a nicotinic brake, Lynx1. Lynx1 shifts a balance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…The effects of lynxes on nicotinic receptor function have so far been determined by heterologous expression systems ( 39, 61 ), knockout studies ( 61, 81 ), exogenous application of recombinant water-soluble lynx proteins ( 86, 87 ), and more recently viral overexpression in the brain ( 42, 88 ). Our results are highlight complex endogenous regulation of optogenetic nicotinic responses by multiple GPI-anchored lynxes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of lynxes on nicotinic receptor function have so far been determined by heterologous expression systems ( 39, 61 ), knockout studies ( 61, 81 ), exogenous application of recombinant water-soluble lynx proteins ( 86, 87 ), and more recently viral overexpression in the brain ( 42, 88 ). Our results are highlight complex endogenous regulation of optogenetic nicotinic responses by multiple GPI-anchored lynxes.…”
Section: Discussionmentioning
confidence: 99%
“…Such flexible tuning of nicotinic responses by lynx prototoxins in Chrna5+ neurons can provide greater dynamic range and poises them to be key players during attentional processing (Fig 9). A recent study found that developmental increase in Lynx1 expression in corticocortical neurons suppressed their nicotinic responses and preventing this by viral knockdown of Lynx1 led to altered cortical connectivity and impaired attention ( 42 ). Thus cell-type specific changes in lynx expression during development are critical for maturation of attention circuits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations